2022
DOI: 10.1002/dmrr.3535
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and multiple myeloma; common features of two distinct entities

Abstract: Diabetes mellitus (DM) has attained the status of a global pandemic. Cardiovascular disease (CV) was the leading cause of morbidity in people with type 2 DM, however, a transition from CV to cancer as the leading contributor to DM related death has been observed lately. Multiple myeloma (MM) is the second most common haematological malignancy. Obesity is a common risk factor for both DM and MM. Although data are limited, studies have shown that DM might be associated with increased risk for the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 138 publications
0
2
0
Order By: Relevance
“… 45 47 Insulin resistance is also a common feature of patients with T2DM and has been linked to an increased risk of various types of HCs, including MM. 48 By reducing insulin resistance and lowering insulin and glucose levels, metformin may help to create an unfavorable environment for the growth and survival of HCs cells. Metformin may also impact the tumor microenvironment by promoting an anti-inflammatory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“… 45 47 Insulin resistance is also a common feature of patients with T2DM and has been linked to an increased risk of various types of HCs, including MM. 48 By reducing insulin resistance and lowering insulin and glucose levels, metformin may help to create an unfavorable environment for the growth and survival of HCs cells. Metformin may also impact the tumor microenvironment by promoting an anti-inflammatory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Although DM might be associated with the development of MM [16] and DM may be an adverse prognostic factor for overall survival in patients with MM [17], data linking DM and MGUS are limited, with conflicting conclusions due to the overlapping effect of obesity [18]. A population-based matched case-control study in Sweden, with 94,579 cases and 368,348 controls, aimed to examine the association between DM and plasma cell dyscrasias as well as lymphoproliferative disorders [19].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…MM is the second most common hematological malignancy after lymphoma [2] and the most common clinical manifestations are hypercalcemia, renal failure, anemia and lytic bone lesions [1]. MM can be associated with some gene mutations, and epidemiological studies have shown its links with aging, male sex, obesity, diabetes mellitus and metabolic syndrome [1,[3][4][5][6][7][8][9]. Dioxin exposure [10,11] and ionizing radiation [12] can also be risk factors but smoking is not [13].…”
Section: Introductionmentioning
confidence: 99%